2020
DOI: 10.1177/0040517520932230
|View full text |Cite
|
Sign up to set email alerts
|

Electro-textile wearable antennas in wireless body area networks: materials, antenna design, manufacturing techniques, and human body consideration—a review

Abstract: The latest progress in the emerging wireless technology has resulted in the development of wearable antennas made of various fabrics. This unique antenna is an integral part of the wireless body area network (WBAN). A wide range of applications are made by the wearable antennas in the fields of the Internet of Things, sport, defense, public safety, telemedicine, navigation, and tracking. The focus point of the current review is the recent progress of electro-textiles research with special attention on the mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…It was found that the quality of the employee service plays a moderating role between RFID and the operation of the textile manufacturing and apparel industry, and it helps practitioners solve related industry problems [11]; Almohammed et al introduced the material properties, standards and manufacturing process of electronic textile manufacturing, and analysed the importance of current electronic textile manufacturing processes and material selection. It was found that the electronic textile manufacturing materials, technology, and design can provide high-performance materials for body-centric applications in the future [12].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the quality of the employee service plays a moderating role between RFID and the operation of the textile manufacturing and apparel industry, and it helps practitioners solve related industry problems [11]; Almohammed et al introduced the material properties, standards and manufacturing process of electronic textile manufacturing, and analysed the importance of current electronic textile manufacturing processes and material selection. It was found that the electronic textile manufacturing materials, technology, and design can provide high-performance materials for body-centric applications in the future [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the application of knit fabrics has expanded from the traditional textile applications to their use in the creation of wearable electronics. From the use of warp knit to create textile antennas to the use of weft knit to create strain sensors, the application of knitting to create conventional electronics is being rapidly adopted [ 1 , 2 , 3 , 4 , 5 , 6 ]. In particular, conductive weft knitted fabrics have been utilised as strain sensors, because of their elastic structure and piezoresistivity [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wearable antennas, as a vital component in WBAN systems, enable wireless communication with other devices on or off human bodies [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Compared to traditional antennas, the design of wearable antennas are facing many development bottlenecks: The electromagnetic coupling between the human body and the antenna, the varying physical deformations, the widely varying operating environments, and limitations of the fabrication process [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional antennas, the design of wearable antennas are facing many development bottlenecks: The electromagnetic coupling between the human body and the antenna, the varying physical deformations, the widely varying operating environments, and limitations of the fabrication process [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Further, the requirements for these wearable antennas include mechanical robustness, low-profile, lightweight, user comfort, fabrication simplicity [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], wideband [ 25 , 26 ], and multiband [ 20 , 27 , 29 ]. Thus, advanced design methods and techniques are urgently needed to address these problems and demands of wearable antennas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation